2020
DOI: 10.1111/ijd.14839
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional immunotherapy with purified protein derivative (PPD) for cryotherapy‐resistant warts

Abstract: BackgroundCryotherapy and immunotherapeutic modalities elicit nonspecific immune response against the human papillomavirus. There is a paucity of literature on the effects of a sequential shift to immunotherapy in cryotherapy‐resistant warts.AimTo study the efficacy of intralesional purified protein derivative (PPD) immunotherapy in cryotherapy‐resistant warts.MethodsPatients with cryotherapy‐recalcitrant cutaneous warts were given intralesional injections of PPD into the index warts (oldest or largest) at 2‐w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 11 publications
6
26
0
Order By: Relevance
“…Additionally, at the end of the follow up period, which extended for 6 months, no patients showed recurrence of lesion that is matching with Abo-Taleb et al (10) and Kaimal et al (15) results. Induction of longterm cell-mediated immunity, which allows the body to recognize HPV, stimulates the production of memory Tcells against the virus, and intensifies effector response mechanisms of memory T-cells against the virus (17) .…”
Section: A B Csupporting
confidence: 88%
“…Additionally, at the end of the follow up period, which extended for 6 months, no patients showed recurrence of lesion that is matching with Abo-Taleb et al (10) and Kaimal et al (15) results. Induction of longterm cell-mediated immunity, which allows the body to recognize HPV, stimulates the production of memory Tcells against the virus, and intensifies effector response mechanisms of memory T-cells against the virus (17) .…”
Section: A B Csupporting
confidence: 88%
“…for the use of PPD in cryotherapy resistant warts and the results were encouraging. 5 Their study outcomes also matches our observations. Jaiswal et al, report clearance in over 68.6% patients.…”
Section: Kaimal Et Al Conducted An Open Labelled Uncontrolled Trialsupporting
confidence: 88%
“…This is the basis for lesion clearance at not only the injection site but also at distant sites. 4,5 We have tried to make use of purified protein derivative in context of Indian population for the management of multiple warts as this treatment modality is easily available and most importantly cost effective.…”
Section: Introductionmentioning
confidence: 99%
“…Amirnia et al reported significantly higher occurrence of blisters with cryotherapy compared with tuberculin immunotherapy 13 . Blister formation is a well‐recognized side effect of cryotherapy as freezing and thawing induces epidermal necrosis with resultant cell oedema and apoptosis 10 . Our rate of this complication was comparable to other studies 8,17 …”
Section: Discussionsupporting
confidence: 75%
“…Non‐responders to immunotherapy might have been included in our cohort as positive skin test was not an inclusion criterion. Immunotherapy response rates of 50% to 62.2% were reported in studies that did not perform skin test as a prerequisite for enrollment 10,11 . Several studies showed that regardless of skin test induration diameter, a standard dose of immunotherapy could be used 11,17,19 and the induration diameter of the skin test was not associated with overall therapeutic response 8 …”
Section: Discussionmentioning
confidence: 99%